2021
DOI: 10.1002/anie.202109082
|View full text |Cite
|
Sign up to set email alerts
|

Forrestiacids A and B, Pentaterpene Inhibitors of ACL and Lipogenesis: Extending the Limits of Computational NMR Methods in the Structure Assignment of Complex Natural Products

Abstract: Forrestiacids A (1) and B (2) are a novel class of [4+2] type pentaterpenoids derived from a rearranged lanostane moiety (dienophile) and an abietane unit (diene). These unprecedented molecules were isolated using guidance by molecular ion networking (MoIN) from Pseudotsuga forrestii, an endangered member of the Asian Douglas Fir Family. The intermolecular hetero‐Diels–Alder adducts feature an unusual bicyclo[2.2.2]octene ring system. Their structures were elucidated by spectroscopic analysis, GIAO NMR calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 29 publications
1
50
0
Order By: Relevance
“…Besides, enriched carbon signals for bipentaromycin E (5) were observed at 20 different carbons in [2-13 C]-sodium acetate feeding experiment, including C2, C4, C6, C8, C12, C14, C16, C18, C20, C22, C2′, C4′, C6′, C8′, C12′, C14′, C16′, C18′, C20′, and C22′ (Figure S13). Further analysis of the 13 C NMR spectrum of [1,[2][3][4][5][6][7][8][9][10][11][12][13] C 2 ]-sodium acetate labeled 3 showed that all carbon resonances except Me-13 were enriched (Figure S13). All except C2, C9, C2′, and C9′ were coupled to one other carbon, in which carbons derived from the same sodium acetate unit shared the same J CC values (Table S7).…”
Section: Deciphering the Biosynthetic Origin Of Bipentaromycin Skeletonmentioning
confidence: 99%
“…Besides, enriched carbon signals for bipentaromycin E (5) were observed at 20 different carbons in [2-13 C]-sodium acetate feeding experiment, including C2, C4, C6, C8, C12, C14, C16, C18, C20, C22, C2′, C4′, C6′, C8′, C12′, C14′, C16′, C18′, C20′, and C22′ (Figure S13). Further analysis of the 13 C NMR spectrum of [1,[2][3][4][5][6][7][8][9][10][11][12][13] C 2 ]-sodium acetate labeled 3 showed that all carbon resonances except Me-13 were enriched (Figure S13). All except C2, C9, C2′, and C9′ were coupled to one other carbon, in which carbons derived from the same sodium acetate unit shared the same J CC values (Table S7).…”
Section: Deciphering the Biosynthetic Origin Of Bipentaromycin Skeletonmentioning
confidence: 99%
“…In total, 11 compounds (C1–C11) were kindly offered by the research group of Professor Hu, which were newly separated from traditional Chinese medicine ( Pseudotsuga forrestii ). [ 29 ] Here, we explored their potential activity to inhibit APN activity based on our new CL strategy. As show in Figure 3b, four compounds showed an obvious inhibitory ability for APN, especially C7 and C8 with the highest inhibitory activity, which indicated they were the potential drug candidates for abnormally elevated APN‐related diseases.…”
Section: Resultsmentioning
confidence: 99%
“…These prenylated indole alkaloids were also found to be inactive (IC 50 s > 20 μM) in the bioassays against PTP1B, ATP-citrate lyase (ACL), and acetyl-CoA carboxylate 1 (ACC1), which are potential drug targets associated with the glycolipid metabolic disorders. 3,9…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, relevant research on the REPs endemic to China have been launched by our group. 3 However, in many cases, it is not easy to investigate endangered species due to the difficulties in collecting the rare plant materials. Fortunately, a large number of endophytic fungi, bacteria and actinomycetes contained in each plant species may be able to synthesize related plant metabolites.…”
Section: Introductionmentioning
confidence: 99%